Positive clinical outcomes following therapy with programmed cell death protein 1/programmed cell death ligand 1 inhibitors in neuroendocrine carcinoma of the cervix - Liu, Rongyu; He, Xinlin; Li, Zhengyu (Frontiers in Pharmacology, 2022)
Neuroendocrine carcinoma of the cervix (NECC) is a highly aggressive and rare gynecological malignancy with a poor prognosis. Despite aggressive local and systemic treatments, there are high rates of locoregional recurrence and distant metastases. Therefore, more potent treatments are required to manage NECC. In recent years, emerging immune checkpoint inhibitors, such as programmed cell death protein 1 (PD-1)/programmed cell death ligand 1 (PD-L1) inhibitors, have been used in treating various solid tumors and provide a new direction for immune-targeted therapy for NECC. In this review, we summarize the biomarkers useful for the evaluation of the therapy with PD-1/PD-L1 inhibitors in patients with NECC and the clinical applications and prospects of monotherapy with PD-1/PD-L1 inhibitors and combinations with other therapies in patients with NECC. In some individual case reports, therapeutic strategies with PD-1/PD-L1 inhibitors showed good efficacy. Further studies are needed to confirm the possibility of using PD-1/PD-L1 inhibitors as a standard treatment strategy in NECC.